3D-conformal Accelerated Partial Breast Irradiation treatment planning: the value of surgical clips in the delineation of the lumpectomy cavity - Dzhugashvili, Maia (BioMed Central, 2009)
BACKGROUND: Accurate localisation of the lumpectomy cavity (LC) volume is one of the most critical points in 3D-conformal Partial breast irradiation (3D-APBI) treatment planning because the irradiated volume is restricted to a small breast volume. Here, we studied the role of the placement of surgical clips at the 4 cardinal points of the lumpectomy cavity in target delineation. METHODS: Forty CT-based 3D-APBI plans were retrieved on which a total of 4 radiation oncologists, two trainee and two experienced physicians, outlined the lumpectomy cavity. The inter-observer variability of LC contouring was assessed when the CTV was defined as the delineation that encompassed both surgical clips and remodelled breast tissue. RESULTS: The conformity index of tumour bed delineation was significantly improved by the placement of surgical clips within the LC (median at 0.65). Furthermore, a better conformity index of LC was observed according to the experience of the physicians (median CI = 0.55 for trainee physicians vs 0.65 for experienced physicians). CONCLUSIONS: The placement of surgical clips improved the accuracy of lumpectomy cavity delineation in 3D-APBI. However, a learning curve is needed to improve the conformity index of the lumpectomy cavity.